Comparative study of conductive polypyrrole and polyaniline coatings on electro-active papers - Kim, Jachwan; Deshpande, S. D.; Yun, Sungryul; Li, Qubo (Polymer Journal, 2006)
{A comparative study is performed on the conductive polymer-coated electro-active paper (EAPap) actuators by aiming at improving the overall performance of the actuators. Conductive Polymer coated Electro-active Paper [
IUPAC Symposium on Ionic Polymerization, Goa, INDIA, OCT 23-28, 2005
Keywords: conifer; glufosinate; particle bombardment; Pinus roxburghii; stable transformation